2005
DOI: 10.4049/jimmunol.175.12.8218
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-Specific CD4+ T Cells in Healthy Carriers Are Continuously Driven to Replicative Exhaustion

Abstract: Repeated antigenic encounter drives proliferation and differentiation of memory T cell pools. An important question is whether certain specific T cells may be driven eventually to exhaustion in elderly individuals since the human life expectancy is increasing. We found that CMV-specific CD4+ T cells were significantly expanded in healthy young and old carriers compared with purified protein derivative-, varicella zoster virus-, EBV-, and HSV-specific populations. These CMV-specific CD4+ T cells exhibited a lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
255
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(277 citation statements)
references
References 55 publications
19
255
3
Order By: Relevance
“…Our finding that, among the agents tested, CMV elicited the greatest responses in the CD127 2 cells, which are relatively abundant in the CCR5 + CCR2 2 subset, is consistent with previous data (58), and suggested that CMV was the virus most often (re)stimulating a systemic immune response. These results are also consistent with data that a large percentage of memory T cells are CMV specific in infected individuals (72)(73)(74), significantly higher than for other herpesviruses (73,75). When taken together, the Ag-specific responses suggest that the ratio of Ag-reactive cells in the CCR5 + CCR2 + versus CCR5 + CCR2 2 subsets reflected the ratio of cells reacting to a given agent that were resting memory versus recently (re) activated-highest for tetanus toxoid and lowest for CMV.…”
Section: Ccr2supporting
confidence: 80%
“…Our finding that, among the agents tested, CMV elicited the greatest responses in the CD127 2 cells, which are relatively abundant in the CCR5 + CCR2 2 subset, is consistent with previous data (58), and suggested that CMV was the virus most often (re)stimulating a systemic immune response. These results are also consistent with data that a large percentage of memory T cells are CMV specific in infected individuals (72)(73)(74), significantly higher than for other herpesviruses (73,75). When taken together, the Ag-specific responses suggest that the ratio of Ag-reactive cells in the CCR5 + CCR2 + versus CCR5 + CCR2 2 subsets reflected the ratio of cells reacting to a given agent that were resting memory versus recently (re) activated-highest for tetanus toxoid and lowest for CMV.…”
Section: Ccr2supporting
confidence: 80%
“…4), thus indicating that CD4 + NKG2D + cells represent only a fraction of HCMV-specific T lymphocytes, as predicted by the phenotypic analyses described above. Attempts to grow CD4 + NKG2D + T cell clones were unsuccessful, suggesting that their proliferative capacity is limited, in line with previous studies showing that HCMV-specific T cells undergo replicative exhaustion [46]. To assess the function of NKG2D, HCMV-stimulated CD4 + T cells were incubated with suboptimal concentrations of anti-CD3 mAb in the presence or absence of anti-NKG2D mAb.…”
Section: Distribution Of Ilt2 Kir and Cd94/nkg2 Nkr On Hcmv-stimulatmentioning
confidence: 83%
“…We and others have previously shown that the presence of CD4 1 CD28 À T cells in patients with RA is strongly associated with CMV infection [47,48]. Indeed, a significant proportion of CD4 1 CD28 À T cells display specificity for CMV antigens and a majority of the CMV-specific CD4 1 T cells lack CD28 [47,49]. Also, several studies indicate increased NKR expression on T cells in CMV-infected individuals [31,50].…”
Section: Discussionmentioning
confidence: 93%